2021
DOI: 10.3389/fnsys.2021.625919
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Patterns of Global Brain Communication Differentiate Conscious From Unconscious Patients After Severe Brain Injury

Abstract: The neurophysiology of the subjective sensation of being conscious is elusive; therefore, it remains controversial how consciousness can be recognized in patients who are not responsive but seemingly awake. During general anesthesia, a model for the transition between consciousness and unconsciousness, specific covariance matrices between the activity of brain regions that we call patterns of global brain communication reliably disappear when people lose consciousness. This functional magnetic imaging study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This has been a practical solution since individual matrices were not provided for all participants. For patients with severe brain injury the classification would possibly improve if these injuries were reflected in connectivity, since alterations within specific brain networks impairs communication among networks [53]. As we observed above, the influence of the SC matrix on LV equations is always multiplied by the activity of the respective networks.…”
Section: Plos Computational Biologymentioning
confidence: 89%
“…This has been a practical solution since individual matrices were not provided for all participants. For patients with severe brain injury the classification would possibly improve if these injuries were reflected in connectivity, since alterations within specific brain networks impairs communication among networks [53]. As we observed above, the influence of the SC matrix on LV equations is always multiplied by the activity of the respective networks.…”
Section: Plos Computational Biologymentioning
confidence: 89%
“…The connectivity and integration across the frontal and parietal cortices have a crucial relationship to both LOC and ROC, whereby the connectivity between these two brain regions is regarded as the foundation for conscious changes during anesthesia (Alkire et al, 2008 ), including sevoflurane-induced unconsciousness. Comparisons of functional magnetic resonance images between patients anesthetized with sevoflurane and those presenting with brain injury showed that a discrepancy between the sensory and motor areas, their overall similarity, and dynamic change were closely associated with complete consciousness linked to the activity of the fronto-parietal network (Golkowski et al, 2021 ). In fact, the whole prefrontal cortex seems to have a significant correlation with consciousness, including the dorsomedial, dorsolateral and ventromedial prefrontal cortices, as measured by fisher scores by using vector machines.…”
Section: Brain Areas and Circuitsmentioning
confidence: 99%
“…The analysis of dynamic or time-resolved functional connectivity, as well as the relationship between the underlying anatomical connections and emergent time-resolved functional connectivity ( Avena-Koenigsberger et al, 2018 ; Suárez et al, 2020 ), may be clinically relevant in patients with DoC. Previous studies have already explored the role of time-resolved functional connectivity in DoC ( Del Pozo et al, 2021 ; Golkowski et al, 2021 ; Sanz Perl et al, 2021 ). A recent study demonstrated that network states with long-distance connections occurred less frequently over time in MCS compared to UWS patients ( Demertzi et al, 2019 ), emphasizing disintegration of interactions across the cortex in unconscious states.…”
Section: Introductionmentioning
confidence: 99%